How strategic is human resource management in Kazakhstan? A survey of how companies manage talented employees / Paul James Davis, Xeniya Pavlova - Davis, Paul James; Pavlova, Xeniya (2012)
The purpose of this paper is to explore the approach toward talent management among Kazakhstani companies and multinational subsidiaries in Kazakhstan. The objective is to understand the extent to which practice in Kazakhstan is congruent with best practice in leading industrialized nations. Data were collected through twelve in-depth interviews with HR managers from different companies. The findings suggest that talent management practices are diverse in the participating companies although Kazakhstani companies generally lag well behind international best practice. The research is highly original being the first study on this topic in Kazakhstan. As such the research fills a gap in the literature and provides some insights for practitioners working in talent management.